PENGEMBANGAN BUKU SAKU Pengembangan Buku Saku Berbasis Flipbook Digital sebagai Media Edukasi Gizi Seimbang untuk Pencegahan Anemia pada RemajaBERBASIS FLIPBOOK DIGITAL SEBAGAI MEDIA EDUKASI GIZI SEIMBANG UNTUK PENCEGAHAN ANEMIA PADA REMAJA - Risda Ervina; Monalisa Monalisa; Gusti Lestari Handayani; Vivinati Dewi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Riskesdas data shows that anemia in Indonesia has increased to 32%. Anemia is closely related to nutrition; in Jambi Province, particularly in Tanjung Jabung Timur Regency, teenagers aged 13–15 have varied nutritional status: 2.04% are severely thin, 7.40% thin, 72.89% have normal nutrition, 8.17% are overweight, and 3.93% are obese. A preliminary study at SMPN 21 Tanjung Jabung Timur involving 26 respondents found that 14 students (69.23%) did not understand the importance of balanced nutrition or the causes and impacts of anemia, indicating that teenager’s nutritional knowledge is still low and requires education. This study aims to develop a digital pocketbook as an educational medium for anemia prevention and to assess its validity and practicality. The method using the DDD-E model (decide, design, develop, evaluate) and was conducted at SMPN 21, Tanjung Jabung Timur Regency. Data was obtained from material, language, and media validation, as well as student questionnaires. The results showed that the material expert gave a score of 4.7, the language expert 4.6, and the media expert 4.75, all of which fall into the “very valid” category. Student responses also showed scores of 4.72 from the small-group trial and 4.85 from the large-group trial, both categorized as “very practical.” In conclusion, this digital pocketbook is “highly valid and very practical” for use.